1987
DOI: 10.1111/j.1469-8986.1987.tb00276.x
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus Omission and Dishabituation of the Electrodermal Orienting Response: The Allocation of Processing Resources

Abstract: The present research investigated the effects of stimulus omission on electrodermal orienting, dishabituation. and the allocation of processing resources as assessed by reaction time (RT) to a secondary probe stimulus. All experiments employed 33 tone‐light or light‐tone (S1‐S2) pairings, and for experimental groups, S2 was omitted on 4 trials, experiment 1 (N = 24) demonstrated reliable electrodermal responding when S2 was omitted for a trial, and subsequent dishabituation when S2 was then re‐presented after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(28 citation statements)
references
References 15 publications
2
26
0
Order By: Relevance
“…In line with this assumption, Siddle and Packer (Packer & Siddle, 1989;Siddle & Packer, 1987) found that RTs to a secondary probe were slower during unexpected trials, indicating that unexpected events indeed demand processing resources. However, these authors did not explicitly address the theoretically important assumption of a linear (or at least monotonic) relationship between the unexpectedness of an event and the amount of processing devoted to it.…”
Section: Interruption Of Ongoing Activitiesmentioning
confidence: 84%
“…In line with this assumption, Siddle and Packer (Packer & Siddle, 1989;Siddle & Packer, 1987) found that RTs to a secondary probe were slower during unexpected trials, indicating that unexpected events indeed demand processing resources. However, these authors did not explicitly address the theoretically important assumption of a linear (or at least monotonic) relationship between the unexpectedness of an event and the amount of processing devoted to it.…”
Section: Interruption Of Ongoing Activitiesmentioning
confidence: 84%
“…The specific hypothesis examined by Dawson et al was that the orienting response is associated with the allocation of limited processing resources (e.g., Siddle & Packer, 1987). Dawson et al tested college students on a dual-task procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The data were range corrected by dividing each participant’s SCR by her maximum response (Lykken and Venables, 1971), in this experiment the highest US response (largest deflection 900–4000 after US onset). A square root transformation was applied to normalize the distribution (Siddle and Packer, 1987). The corrected SCRs were averaged across two trials resulting in five acquisition and five extinction blocks per stimulus.…”
Section: Methodsmentioning
confidence: 99%